A análise da BNCC de língua inglesa: multiletramentos - Santos, Iane da Silva (2020)
This research seeks to analyze the Common National Curriculum Base (BNCC), which, released in 2017, is a mandatory document that aims to guarantee the necessary curriculum components for Basic Education, in which the English Language (LI) has remained as a mandatory foreign language. The objective of this dissertation is to analyze what the BNCC perspectives are, taking into account the teaching-learning goals, specifically related to the teaching of LI in the perspective of multi-tools and multimodality. Thus, the contents chosen by the Base for foreign language teaching and their social implications and citizen education are analyzed, as well as comparisons between the Base and the previous official documents, which will continue to serve as parameters for national education. After this stage, an English language textbook will be analyzed, as support for the analysis of the Base, observing if the contents (description of the textual genres covered) and the BNCC ideals are already being contemplated and how they could be modified to better serve the precepts of that document. The qualitative analysis has the support of theorists who discuss the different topics that arise when emerging in the details of BNCC, such as Cope e Kalantzis (2006, 2008, 2009, 2018), Oliveira (2014), Tagata (2017), Oliveira e Dering (2018), Araújo e Larré (2018), among other authors. The results show that the theory of multi-courses is directly interconnected with the new needs of education, due to its innovative character in the perspective of reading and understanding of digital, critical and media literacies, among others. In this context, the research also found that even with the innovation of theories and new documents, education still remains challenging due to the absence of external and material factors that would facilitate and make English language teaching in public and private institutions more captivating.